Student Performance in Higher Educational Institutions: A Comparative Analysis based on Student Activities and Behaviors - Rupasingha, Hiruni; Silva, Rangika (Asian Journal of Multidisciplinary Studies, 2021)
Today university students are engaging with different activities and they have various behaviors as well. The final result of the student varies based on this highly complicated and competitive environment. Assessing one’s performance, identifying one’s uniqueness and gathering solutions are all challenging problems for university students as well as lecturers. The main focus of the study should be on how student performance changes as a result of their activities. This study compared student academic performance with their hobbies, extracurricular activities, different university activities and behaviors. Data were gathered from graduates of the Sabaragamuwa University of Sri Lanka and used as a sample in this study around 200 graduate students’ responses through an online Google form. Descriptive analysis and multiple regression analysis were used to analyze the data. Based on the analysis results, students who regularly do past papers, regularly attend lectures, and make short notes have obtained a higher class. In comparison to the other students, those who followed extra courses before the university entrance or during the university period also had good grades. When looking at the behavior of students in their regular lifestyle, those who use social media often have a middle-level achievement in their degree. Extracurricular activities have not been significantly impacted. The majority of students who has better results collected their additional knowledge through the Internet. Students who have better results at the university entrance exam for general English could obtain a higher class in their degree. Based on the analysis result research identified that student performance can be improved by group discussions, exchanging experiences with others, various academic sessions, and seminars. Providing free Internet facilities and e-library facilities will be more helpful to improve their knowledge and giving feedback for their examinations in the early stages is also identified as an important task.